INNOVATIVE WAQF MODELS FOR SUSTAINABLE ECONOMIC DEVELOPMENT: ASSESSING LEGAL FRAMEWORKS AND PRACTICES IN INDONESIA CONTEXT - Riyan Al Fajri (CV. Radja Publika, 2025)
This study addresses the significant potential of waqf assets in Indonesia, which are currently underutilized due to a primary focus on charitable and religious purposes, thereby limiting their contribution to sustainable economic development. The aim of the study is to explore how waqf can contribute to economic growth, identify new models for using waqf, and suggest ways to overcome the challenges in waqf development. Using a legal research approach, the study analyzes legal frameworks, reviews existing literature, and compares waqf practices, gathering data from legal sources, academic articles, and policy reports. The findings show that while waqf could significantly boost Indonesia's economy, issues like weak legal support, lack of transparency, and limited skills among waqf managers hold back progress. Innovative models, such as cash waqf linked sukuk, blended finance waqf and crowdfunding waqf, are proposed as effective solutions. In conclusion, to fully realize waqf's potential for sustainable economic growth, comprehensive reforms are needed, including improving the skills of waqf managers, increasing transparency, and updating legal frameworks. By adopting new financing models and encouraging public participation, waqf can become a vital part of inclusive economic development in Indonesia.